Convergence of Electronic Structure Properties in Ionic Oxides Within a Fragment Approach - Larsson, Ernst D.; Veryazov, Valera (Frontiers in Chemistry, 2022)
Embedded-cluster models of crystalline solids are important to allow accurate wave function methods to be applicable to solids. The ab-initio model potential method, in which the crystal is divided into three different fragments, one quantum fragment, one ab-initio model potential fragment and one point-charge fragment, has historically been shown to be a viable tool for describing the electronic structure in ionic solids. The optimal size of these regions is, of course, individual for each crystal. In this study we analyzed the convergence of the electronic structure properties with respect to an increase of the size of the quantum part and the layer of potentials. MgO crystal and Ni:MgO were used for this purpose as examples of an ideal crystal and a crystal with a point defect. We demonstrated that with an increase of the cluster size, the electron density in the inner part of the cluster becomes very similar to the electron density in the periodic model. Clusters, embedded into a layer of model potential and electrostatic field, are a good alternative to periodic description.